Performance and characterization of safflower biodiesel in blends with pure diesel in a motor-generator set (Research, Society and Development, 2023)
Fossil fuel consumption has been decreasing in recent years, however, world electric demand only increases with population growth. It is important to have alternative and less polluting ways of generating energy, among which is biodiesel, which can be obtained from different energy crops, such as safflower (Carthamus tinctorius L.). Viscosity and flash point directly affect engine performance, so it is important to reduce the values of these parameters in the bi-diesel. The objective of this work is to evaluate and characterize the production of biodiesel from safflower seeds, identifying the yield of the process and the efficiency of energy generation of the biofuel, as well as the specific consumption of the engine. The production process of obtaining biodiesel from safflower seeds was evaluated, building a flowchart with mass balance. The characteristics of the cake, oil and biodiesel resulting from the process were analyzed. And evaluated the specific consumption and energy generation of blends B00, B05, B10, B20, B30, B40, B50, B60 and B100, finding that there is no significant difference for the specific consumption and energy generation between the blends in the evaluated loads, showing significant differences only in relation to diesel.